PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH, KOMPETENSI SUMBER DAYA MANUSIA DAN PENGAWASAN FUNGSIONAL TERHADAP EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kota Pekanbaru) - Joni Iskandar; Vince Ratnawati; Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the influence of the government internal control System, the human resources competencies and functional control on the effectiveness of the financial management area. This study was conducted at SKPD of Pekanbaru city. The population in this study were employed who worked in the SKPD Pekanbaru city (32 government agencies). The sampling method used in this study is purposive sampling method. The respondent in this study is the head of SKPD, the head of financial, treasurer of SKPD and PPTK SKPD. The sample used in this study were 120 respondents. The hypotheses then tested is multiple linear regression analysis by using SPSS version 20.0. The result of this study indicated that the government internal control System, the human resources competencies and functional control has significantly effect on effectiveness of the financial management area. The magnitude of the effect (R2) the government internal control System, the human resources competencies and functional control on the effectiveness of the financial management area was 48,5%. While the remaining 51,5% is influenced by other independent variabel that are not observed in this study.Keywords: internal control, competencies, functional, effectiveness and government